Analysis of fungal high-mannose structures using CAZymes. (22nd December 2021) - Kołaczkowski, Bartłomiej M; Jørgensen, Christian I; Spodsberg, Nikolaj; Stringer, Mary A; Supekar, Nitin T; Azadi, Parastoo; Westh, Peter; Krogh, Kristian B R M; Jensen, Kenneth
Abstract: Glycoengineering ultimately allows control over glycosylation patterns to generate new glycoprotein variants with desired properties. A common challenge is glycan heterogeneity, which may affect protein function and limit the use of key techniques such as mass spectrometry. Moreover, heterologous protein expression can introduce nonnative glycan chains that may not fulfill the requirement for therapeutic proteins. One strategy to address these challenges is partial trimming or complete removal of glycan chains, which can be obtained through selective application of exoglycosidases. Here, we demonstrate an enzymatic O -deglycosylation toolbox of a GH92 α-1, 2-mannosidase from Neobacillus novalis, a GH2 β-galactofuranosidase from Amesia atrobrunnea and the jack bean α-mannosidase. The extent of enzymatic O -deglycosylation was mapped against a full glycosyl linkage analysis of the O -glycosylated linker of cellobiohydrolase I from Trichoderma reesei ( Tr Cel7A). Furthermore, the influence of deglycosylation on Tr Cel7A functionality was evaluated by kinetic characterization of native and O -deglycosylated forms of Tr Cel7A. This study expands structural knowledge on fungal O -glycosylation and presents a ready-to-use enzymatic approach for controlled O -glycan engineering in glycoproteins expressed in filamentous fungi.